Analisis laporan realisasi anggaran sebagai penilaian terhadap kinerja keuangan pada kantor inspektorat pembantu wilayah kerja Jakarta Barat - Gurhanawan, Gurhanawan (ARKA INSTITUTE, 2023)
Budget Realization Report is a form of financial report issued by the government or agency before making a balance sheet report and cash flow report. The purpose of this study is to analyze the inspectorate's budget realization report consecutively from 2020 - 2022 by looking at three aspects, namely spending variants, economic levels and spending efficiency ratios. This study uses a quantitative descriptive method, in which the data collected is compiled, analyzed and interpreted by describing the results obtained. The results of the analysis show that the financial performance of the Assistant Inspectorate for the West Jakarta Working Area has increased significantly. So it can be concluded that the financial performance of the Assistant Inspectorate for the West Jakarta Working Area can be said to be good.